Radio frequency animal identification: electromagnetic analysis and experimental evaluation of the transponder-gate system. (21st August 2006) - Alu, Andrea; Sapia, Carmine; Toscano, Alessandro; Vegni, Lucio
In this paper we present some theoretical and experimental results in the investigation of the electromagnetic setup for Radio Frequency Identificaiton (RFID), that is, a complex environment in which a reader–transponder system operates for the recognition and classification of animals. This kind of system is becoming very popular in some market branches (e.g. the bovine meat market) and we present here also an experimental analysis of the bovine meat process steps, localising possible sources of electromagnetic noise in the standardised frequency range of RFID. In particular, the system under analysis is composed of a portable reader (Innoceramics P3000) and passive glass tags (boli) working in Half-Duplex (HDX) at frequencies of 123.2 kHz and 134.2 kHz (field strength ~106 dbµV/m, reading distance about 25 cm).